2016
DOI: 10.1002/andp.201600080
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the Robin quantum wall in a linear potential. I. Energy spectrum, polarization and quantum‐information measures

Abstract: Information-theoretical concepts are employed for the analysis of the interplay between a transverse electric field E applied to a one-dimensional surface and Robin boundary condition (BC), which with the help of the extrapolation length Λ zeroes at the interface a linear combination of the quantum mechanical wave function and its spatial derivative, and its influence on the properties of the structure. For doing this, exact analytical solutions of the corresponding Schrödinger equation are derived and used fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 94 publications
2
42
0
Order By: Relevance
“…for the finite nonzero extrapolation length Λ is determined from the transcendental equation [2] 2meE 2…”
Section: Introductionmentioning
confidence: 99%
“…for the finite nonzero extrapolation length Λ is determined from the transcendental equation [2] 2meE 2…”
Section: Introductionmentioning
confidence: 99%
“…Another method to arrive at it is to zero the denominator in Equation (56) what results in infinite specific heat at the transition point. This highly asymmetric cusp-like shape of the specific heat was intensively analyzed theoretically [4,5,65,67,69,70,[91][92][93][94] and demonstrated experimentally. At the infinite number of bosons, N = ∞, the cusp-like shape at T = T cr becomes a discontinuity disclosing in this way a phase transition; namely, in this particular situation, it is a transition from the BE condensate to the normal phase of the noninteracting corpuscles in the asymmetric Robin QW.…”
Section: Bosonsmentioning
confidence: 93%
“…and for the canonical ensemble it is expressed with the help of the fluctuationdissipation theorem: [1] c can (β) = β 2 E 2 can − E 2 can (5) For N noninteracting particles in the system, the right-hand sides of Equations (2)-(5) have to be multiplied by N. Recent comparative analysis of the 1D quantum well (QW) with miscellaneous permutations of the Dirichlet and Neumann boundary conditions (BCs) [2] confirmed that the energy spacing between the orbitals δ E n = E n+1 − E n (6) plays a crucial role in the thermodynamic properties dependence on temperature; in particular, since this quantity is, at the fixed n (specifically, at n = 0), the smallest for the pure Neumann structure as compared to other two geometries, [3] its heat capacity exhibits a salient maximum as a function of T accompanied by the broad minimum at higher temperatures whereas for any other BC configuration the c V −T characteristics is a smooth line. [2] www.advancedsciencenews.com www.ann-phys.org…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations